2011
DOI: 10.1007/s10897-011-9359-8
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Family History Questionnaires: An Examination of Genetic Risk Estimates and Genetic Testing Eligibility in the Non‐responder Population

Abstract: The use of mailed family history questionnaires (FHQs) has previously been established to be an effective method for obtaining family history information for the triage of patients for genetic counseling and genetic testing of hereditary breast and ovarian cancer syndrome; yet only 53% of patients complete their FHQ within 6 months from the date of mailing (Armel et al. Journal of Genetic Counseling, 18(4):366-378, 2009). Although literature exists evaluating why women may not attend genetic counseling, no dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 23 publications
2
10
0
2
Order By: Relevance
“…Ce préalable implique qu'une personne, dont la probabilité qu'elle soit porteuse de la mutation est élevée, soit en vie, accepte que son dossier médical soit transmis à un généticien et accepte le principe de l'analyse molé-culaire ; si la mutation est identifiée et son caractère délétère documenté, elle accepte alors de diffuser elle-même l'information dans sa famille, la préservation de la confidentialité et du secret médical étant indispensable [4]. Or, beaucoup de patients ne sont pas prêts à transmettre ce message pour diverses raisons, qui tiennent à leur difficulté à parler de leur propre histoire, à leur souhait de parcourir seul un chemin douloureux, à l'impossibilité de comprendre ou d'accepter que d'autres membres de leur famille pourraient être confrontés à une situation comparable, ou plus simplement à la mésentente familiale, qui est loin d'être exceptionnelle [5].…”
Section: Grands Principesunclassified
“…Ce préalable implique qu'une personne, dont la probabilité qu'elle soit porteuse de la mutation est élevée, soit en vie, accepte que son dossier médical soit transmis à un généticien et accepte le principe de l'analyse molé-culaire ; si la mutation est identifiée et son caractère délétère documenté, elle accepte alors de diffuser elle-même l'information dans sa famille, la préservation de la confidentialité et du secret médical étant indispensable [4]. Or, beaucoup de patients ne sont pas prêts à transmettre ce message pour diverses raisons, qui tiennent à leur difficulté à parler de leur propre histoire, à leur souhait de parcourir seul un chemin douloureux, à l'impossibilité de comprendre ou d'accepter que d'autres membres de leur famille pourraient être confrontés à une situation comparable, ou plus simplement à la mésentente familiale, qui est loin d'être exceptionnelle [5].…”
Section: Grands Principesunclassified
“…While clearly desirable to both patients and genetic counselors, a number of studies have also confirmed that a self-administered FHQ is an accurate tool for the systematic collection of family history information (Armel et al 2009;Qureshi et al 2009;Vogel et al 2012). Furthermore, FHQs have been demonstrated to be effective in triaging patients for genetic counseling and assessing genetic risk; however, despite these recognized benefits, response rates to mailed FHQs remain low, ranging from 25 to 53 % (Armel et al 2009(Armel et al , 2011Chalmers et al 2001;Leggatt et al 1999;Mancuso et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In two small telephone surveys, 89 and 63 % of patients that did not complete a mailed FHQ reported that they intended to, confirming a definitive gap between intent and actual response (Appleby-Tagoe et al 2012;Poplawski et al 2009). In an attempt to understand reasons for non-response, two Canadian studies reported that the most commonly cited reasons for non-completion were related to being busy, procrastinating, having limited access to family history information, and bad timing (Appleby-Tagoe et al 2012;Armel et al 2011). Of interest, non-completion of the FHQ was not attributed to lack of perceived benefit of genetic counseling or lack of perceived risk of cancer; only 7 % of patients reported that uncertainty about having genetic counseling and testing attributed to their non-response (Armel et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations